1979
DOI: 10.1530/acta.0.0900139
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cyclic Nucleotides in the Adrenal Gland

Abstract: Effects of ACTH and calcium on cyclic AMP and steroid production by the zona fasciculata-reticularis (the decapsulated fraction) from the rat adrenal cortex have been studied. Increasing concentrations of extracellular calcium enhanced the action of ACTH on cyclic AMP and steroid production. These effects of ACTH with calcium were prevented by lanthanum, but not by tetracaine or verapamil, suggesting that ACTH stimulation may be mediated by calcium through a process not involving the tetracaine- or verapamil-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
1

Year Published

1979
1979
2000
2000

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…The present experiment also confirmed that an increase in cyclic AMP by calcium-deprivation occurred not in the decapsulated fraction (Shima et al, 1979) but only in the capsular. No increase in the medullary cyclic AMP of the rat adrenal gland was also observed by omission of calcium from the incubation medium (Shima et al, 1977). Rubin et al (1972) have reported on an increase in the whole adrenal cyclic AMP accumulation by removal of calcium from the medium.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The present experiment also confirmed that an increase in cyclic AMP by calcium-deprivation occurred not in the decapsulated fraction (Shima et al, 1979) but only in the capsular. No increase in the medullary cyclic AMP of the rat adrenal gland was also observed by omission of calcium from the incubation medium (Shima et al, 1977). Rubin et al (1972) have reported on an increase in the whole adrenal cyclic AMP accumulation by removal of calcium from the medium.…”
Section: Discussionsupporting
confidence: 87%
“…Raising calcium concentrations in the medium increased cyclic AMP accumulation as seen in the decapsulated fraction (Shima et al, 1979), suggesting a stimulatory action of external calcium on the cell surface coupled to adenylate cyclase in the membrane independently of ACTH receptors. It is also of interest that unlike the decapsulated fraction, high concentrations of calcium itself were stimulatory to the capsular steroidogenesis (Fig.3).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations